2021
DOI: 10.3389/fmicb.2021.518791
|View full text |Cite
|
Sign up to set email alerts
|

Construction of Mycoplasma hyopneumoniae P97 Null Mutants

Abstract: Mycoplasma hyopneumoniae is the causative agent of enzootic pneumonia, a world-wide problem in the pig industry. This disease is characterized by a dry, non-productive cough, labored breathing, and pneumonia. Despite years of research, vaccines are marginally effective, and none fully protect pigs in a production environment. A better understanding of the host-pathogen interactions of the M. hyopneumoniae-pig disease, which are complex and involve both host and pathogen components, is required. Among the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…Importing the RecA protein from E. coli improved the obtention of bacterial recombinants in Mycoplasma mycoides subsp. capricolum ( 89 ) and in M. hyorhinis ( 90 ), but not in M. hyopneumoniae ( 91 ). Recently, a RecET-like system from B. subtilis was used for targeted gene inactivation or gene replacement in Mycoplasma pneumoniae ( 25 ) and M. gallisepticum ( 23 ).…”
Section: Discussionmentioning
confidence: 95%
“…Importing the RecA protein from E. coli improved the obtention of bacterial recombinants in Mycoplasma mycoides subsp. capricolum ( 89 ) and in M. hyorhinis ( 90 ), but not in M. hyopneumoniae ( 91 ). Recently, a RecET-like system from B. subtilis was used for targeted gene inactivation or gene replacement in Mycoplasma pneumoniae ( 25 ) and M. gallisepticum ( 23 ).…”
Section: Discussionmentioning
confidence: 95%
“…P97 has received the most attention in the P97 adhesin family due to its special repeat regions 1 and 2 (R1 and R2). It has been demonstrated that the R1 repeats region for P97 with a number varying from 9 to 15 of the R1 repeating units (sequence AAKPV[E]) is essential for its host binding (Clampitt et al, 2021; Hsu & Minion, 1998; Minion et al, 2000). Mhp271, a paralog of P97, is the only other M. hyopneumoniae protein containing R1 and R2 repeats associated with the adhesion process (Deutscher et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…
Porcine enzootic pneumonia (PEP) is caused by Mycoplasma hyopneumoniae (M. hyopneumoniae), which is characterized by dry coughing, severe respiratory distress, and growth reduction (Clampitt et al, 2021;Maes et al, 2018). This infection is highly prevalent, ranging between 38% and 100% in almost all areas of pig production worldwide, and causes significant economic losses (Maes, Sibila, et al, 2021).M.
…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…M. ovipneumoniae has the closest genetic relationship withMycoplasma hyopneumoniae (M. hyopneumoniae ) (Clampitt, Madsen, & Minion, 2021). In M. hyopneumoniae , P97 and P102 are not only adhesin molecules that mediate the adhesion, colonization and pathogenesis of host cells, but also the most important immunogen molecules, which can effectively induce the immune response of the body (Raymond et al, 2013; L. K. .…”
Section: Introductionmentioning
confidence: 99%